Prarticle swarm motion synchronization based on the surface graph - Gorda, O.; Serdiuk, A. (Проблеми керування та інформатики, 2024)
The paper considers the task of controlling a group of unmanned aerial vehicles (UAVs) to organize swarm movement along a given trajectory, ensuring the most efficient achievement of the flight goal. У статті розглядається керування групою безпілотних літальних апаратів (БПЛА) для організації руху рою заданою траєкторією, що забезпечує найбільш ефективне досягнення мети польоту.